Aspek Kemanusiaan Dalam Hukuman Qiṣāṣ - Ach. Fuad Fahmi; Martin Putra Perdana; Imam Kamaluddin; Mohammad Nurhadi (Ijtihad, 2021)
Aspect of Humanity in Qiṣāṣ punishment. This paper aims to analyze and describe the human aspects involved in qisas punishment. This literature study uses a qualitative approach by exploring the scientific treasures that are in the turots books related to qisas law. The results of this study indicate that qisas punishment, which is often assumed to be cruel punishment, actually has a significant deterrent effect on the perpetrators of murder (al-qatlu bil qatli). The qisash punishment basically prioritizes the values and aspects of humanity, because this law is based on the text of the al-quran, which is different from human rights (HAM) which prioritizes rationality rather than laws which are especially sourced from the al-Qur'an. Several things that prove the human aspect in qisash punishment include; the death penalty is part of qiṣāṣ, but not all qiṣāṣ penalties end in the death penalty. This can be seen in the human dimension in qishash; Life assurance, forgiveness of the victim's family, and achieving justice in it. Therefore, Islamic law researchers should develop their research through various perspectives, including from the point of view of the main sources of Islamic law, namely al-Qur'an and al-Hadith and related to contemporary problems without contradicting the 2 sources of Islamic law.